Socialization of Occupational Health and Safety Implementation in Transportation Activities for Passengers Experiencing Low-Back Pain on Inter-City Inter-Provincial Buses (AKAP) - Adenan, Adenan; Nurtsaltsiyah, Metiani (Jurnal Kesehatan, 2023)
Introduction: Economic needs make bus drivers pay less attention to safety and health factors while driving. Inter-City Inter-Province Bus (AKAP) as a mode of mass transportation must meet Occupational Health and Safety (OHS) requirements in various aspects. In addition to maintaining the health and safety of all bus passengers and crew, the application of OHS serves to maintain the reliability of the transportation system. This study aims related disease at risk with bus drivers is Low Back Pain because of long time sitting position with non-ergonomic seat also little opportunity to move or relax during the trip. The aim is to increase knowledge about techniques to reduce LBP for bus drivers. This activity is a socializing technique to minimize low back pain (LBP). Method: Qualitative descriptive research methods, data collection techniques are carried out by observation, interviews, and documentation techniques. Results: This activity was carried out with the stage that is for socialization. Conclusion: For the implementation of OHS program for AKAP passenger buses, it has been carried out with applicable standards, but for facilities and infrastructure in the vehicle, it must be completed on all vehicles that are eligible to operate according to AKAP passenger bus standard.